Sensitivity of Tropical Cyclone Tracks and Intensity to Ocean Surface Temperature: Four Cases in Four Different Basins - Ren, Diandong; Lynch, Mervyn; Leslie, L.; Lemarshall, J. (Wiley-Blackwell Publishing, Inc., 2014)
This study investigates the sensitivity of tropical cyclone (TC) motion and intensity to ocean surface fluxes that, in turn, are directly related to sea surface temperatures (SSTs). The Advanced Research version of the Weather Research and Forecast (WRF-ARW) model is used with an improved parameterisation of surface latent heat flux account for ocean salinity. The WRF-ARW simulations compare satisfactorily with the NCEP/NCAR reanalysis for atmospheric fields and remotely sensed precipitation fields, with the model providing details lacking in coarse resolution observations. Among four TCs investigated, except the one re-developed from a previous TC remnant, the stretching term dominates the relative vorticity generation, and a bottom-up propagation mechanism holds for the three TCs. For the Tropical Rainfall Measuring Mission (TRMM) precipitation, the spatial ranges are accurate but actual rainfall rates are significantly larger than those remotely sensed. This indicates the value of numerical simulation in quantitative rainfall precipitation estimation (QPE) for TCs. Sensitivity experiments are performed with altered SSTs and changes in tracks and intensity are examined. A TC-dependent threshold wind speed is introduced in defining total kinetic energy, a measure of TC intensity, so arbitrariness in domain setting is avoided and inter-basin comparisons are possible. The four TCs selected from different global basin show that the intensity increases with increasing SST.Within a domain, a power–law relationship applies. More important, warmer SST indicates a more rapid intensification, quicker formation and reduced warning issuance time for emergency services. The influence of SSTs on TC track is more complex and lacks a generic relationship. For the South Pacific basin, higher SSTs favour a more northerly track. These TCs occasionally cross continental Australia and redevelop in the southern Indian Ocean basin, affecting the resource-rich onshore and offshore industrial developments in northwest Western Australia. In the Atlantic basin (e.g. Katrina 2005), when SSTs increase, the TC tracks tend to curve over warm pools but generally have a shorter ocean-residence time. When the synthesised SST fields are raised 2°C above Katrina (i.e. >32°C), the possibility exists of generating two TCs in close proximity. That lack of unanimity of the impacts on TC tracks, in response to synthesised SSTs, partly arises from the complicated response of subtropical highs, which may be disintegrated into several pieces and dispersed with relatively lower pressure regions, which may become the shortcuts when a TC traces the periphery of the subtropical high.